Experimental investigation of a triple pontoon wave energy converter and breakwater hybrid system. Issue 14 (22nd May 2021) - Peng, Wei; Zhang, Yingnan; Zou, Qingping; Yang, Xueer; Liu, Yanjun; Zhang, Jisheng
Abstract: In this paper, a novel hybrid wave energy converter (WEC)‐floating breakwater system consisting of three floating pontoons with power take‐off (PTO) modules is developed to extract wave energy from heave motion and attenuate waves to protect the coast. Unlike previous studies of this subject, the present three pontoons are in close proximity so that they may share the same foundation to reduce the cost further and both pontoons with step change drafts and same drafts are investigated. A systematic experimental study was carried out in a wave flume to examine the hydrodynamic characteristics of the hybrid system under regular waves. The experimental results are used to assess the influences of the WEC‐breakwater integration and the configuration of pontoons on the hydrodynamic performance of the hybrid system as a WEC and a breakwater. It was found that the integration of multiple energy‐extracting pontoons is robust in smoothing out the power output fluctuations, and the floating pontoons with same drafts gave arise to higher energy conversion efficiency while the floating pontoons with step change drafts are more effective in attenuating wave energy. A parametric analysis is able to identify the balanced performance of the system as a WEC and a breakwater.